The Lingering Now (O agora que demora). Our Odyssey II, by Christiane Jatahy. (Revista Educação, Artes e Inclusão, 2024)
This article, devoted to the performing arts, is dedicated to The Lingering Now (O agora que demora). Our Odyssey II, the new multimedia and multiform play by Christiane Jatahy. This creation corre-sponds to the second volume of a diptych inspired by the Homeric Odyssey. It follows from Ithaca. OurOdyssey I. What does this director intend to showwith her most recentcreation and how does she do it? This is the problem that we intend to answer in our paper. Therefore, our study will be divided into three parts. The first intends to analyze the referred spectacle, stratum by stratum, from its gen-esis to its scenic realization. The second part will address the singularity of the actors' staging, which Christiane Jatahy demands from the castwith whom she works. Regarding the third part, it will turn to the analysis of the role of the viewer, the matrix of the dramaturgical research of this Brazilian creator. Throughout the development of our article, we try to show to what extent the Homeric myth comes to questionlife, both the intimate life of Christiane Jatahy and the contemporary life in general. Theater appears as an act of resistance against the political oppression.
Keywords: travel; exile; politics; intersemioticity